Business Development to Increase Company Performance and Downstream for Nickel-Based Industry - Emarson Singarimbun, Loi; Wicaksono, Agung (The Indonesian Journal of Business Administration, 2017)
Abstract. PT Indonesia Morowali Industrial Park (IMIP) located in Morowali, Central Sulawesi, Indonesia and established in 2013. IMIP is a combination of an Indonesian company with companies from China, where products of IMIP will be exported to China. The Indonesian government made a policy that mining companies can no longer export raw materials from mining output, but the companies should downstream the raw materials if they want to export the results of its products. There are some problems in the PT. Indonesia Morowali Industrial Park (IMIP), including the effect of government regulation of the downstream of the mining, the impact of the construction of smelter in IMIP, strategies that must be implemented to improve the company's performance, strategy that must be built in relation to the downstream undertaken by the company, and priority should be taken based on the strategy that has been selected. Analytical hierarchy process is carried out to see the priority that should be done by the company in selecting alternative strategies. The factors that considered for every alternative are the factor of cost, time, and also the effectiveness of each strategy chosen. Companies do not have to implement all the strategies that have been planned simultaneously, but can execute a strategy according to which the main priorities toward a strategy that has the lowest priority.Keywords: IMIP, Business Development, Analytical Hierarchy Process